1998
DOI: 10.1246/bcsj.71.467
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Arylation of Azole Compounds with Aryl Halides in the Presence of Alkali Metal Carbonates and the Use of Copper Iodide in the Reaction

Abstract: The reactions of iodobenzene with azole compounds, 1,2-disubstituted imidazoles and 2-substituted oxazoles and thiazoles, were examined in the presence of catalytic amounts of Pd(OAc)2 and PPh3 in DMF using alkali metal carbonates as bases. It was found that the coupling products, 5-arylazoles, could be selectively produced in good yields by using Cs2CO3. In the case that their 2-position is unsubstituted, the site could also be arylated. In reactions using bromobenzene in place of iodobenzene, K2CO3 was also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
224
1
8

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 468 publications
(238 citation statements)
references
References 23 publications
1
224
1
8
Order By: Relevance
“…3 It was found that in the presence of catalytic amounts of Pd(OAc) 2 and PPh 3 in DMF, the coupling products, 5-arylated azoles 17, can be synthesized selectively in good yields. 3 Interestingly, it was shown that the addition of stoichiometric Cu(I) salt significantly increases reactivity of the C-2 position of azoles leading to 2-arylated products 18. Although the trend of reactivity in the electrophilic reactions of the azole ring is known to be C-5>C-4>C-2, in the presence of CuI alone (no Pd catalysis), a substantial amount of C-2 substituted product formed, which was attributed to an alternative operating mechanism.…”
Section: Reactions Involving Pd 0 /Pd II Manifold: Synthetic Applicatmentioning
confidence: 99%
See 4 more Smart Citations
“…3 It was found that in the presence of catalytic amounts of Pd(OAc) 2 and PPh 3 in DMF, the coupling products, 5-arylated azoles 17, can be synthesized selectively in good yields. 3 Interestingly, it was shown that the addition of stoichiometric Cu(I) salt significantly increases reactivity of the C-2 position of azoles leading to 2-arylated products 18. Although the trend of reactivity in the electrophilic reactions of the azole ring is known to be C-5>C-4>C-2, in the presence of CuI alone (no Pd catalysis), a substantial amount of C-2 substituted product formed, which was attributed to an alternative operating mechanism.…”
Section: Reactions Involving Pd 0 /Pd II Manifold: Synthetic Applicatmentioning
confidence: 99%
“…It was proposed that exchange of the most acidic proton at C-2 with Cu results in an organocopper intermediate, which is enabled to undergo cross-coupling with aryl halide to form C-2 arylated product 18 (Scheme 9). 3 Furthermore, Miura reported a method for palladium-catalyzed multiple arylation of thiophenes 19 and 22 (Scheme 10). 25 Thiophene carboxamides were shown to undergo triarylation, accompanied by formal decarbamoylation in the presence of Pd(OAc) 2 , Buchwald's ligand (P(o-biphenyl)( t Bu) 2 ) or P( t Bu) 3 , and Cs 2 CO 3 in refluxing xylene.…”
Section: Reactions Involving Pd 0 /Pd II Manifold: Synthetic Applicatmentioning
confidence: 99%
See 3 more Smart Citations